2018
DOI: 10.1016/j.expneurol.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of axon connectivity across a spinal cord transection in rats treated with epidural stimulation and motor training combined with olfactory ensheathing cell transplantation

Abstract: Olfactory ensheathing cells (OECs) are unique glia that support axon outgrowth in the olfactory system, and when used as cellular therapy after spinal cord injury, improve recovery and axon regeneration. Here we assessed the effects of combining OEC transplantation with another promising therapy, epidural electrical stimulation during a rehabilitative motor task. Sprague-Dawley rats received a mid-thoracic transection and transplantation of OECs or fibroblasts (FBs) followed by lumbar stimulation while climbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 68 publications
2
19
0
Order By: Relevance
“…The effects of transplanted OECs were observable after acute than delayed transplantation. However, current studies demonstrated that chronic transplants are still efficient in the improvement of recovery during SCI [97][98][99]. Nevertheless, some studies did not find any significant neuroprotective/regenerative role of OECs in SCI [82,[100][101][102].…”
Section: Transplant Cells From Neural Originmentioning
confidence: 84%
“…The effects of transplanted OECs were observable after acute than delayed transplantation. However, current studies demonstrated that chronic transplants are still efficient in the improvement of recovery during SCI [97][98][99]. Nevertheless, some studies did not find any significant neuroprotective/regenerative role of OECs in SCI [82,[100][101][102].…”
Section: Transplant Cells From Neural Originmentioning
confidence: 84%
“…The second approach is based on promoting neuroregeneration by enhancing axonal regrowth or replacing lost cells (Ahuja et al., 2020). Indeed, based on several experimental paradigms, studies have reported that functional recoveries can be promoted after SCI in rodents by using neurotrophic factors infusion, cell transplantation, peripheral nerve graft, or combination of different treatments (Decherchi et al., 1997; Kanno et al., 2014; Thornton et al., 2018). In Humans this second approach is mainly based on cell transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…While various complementary treatments such as neural stem cell transplantation, neural growth factor injection, and biomedical engineering (e.g., use of tissue scaffolds) can be administered to patients, satisfactory results have not been achieved for these treatments (2). Epidural electrical stimulation (EES) has been reported to restore rhythmic lower-limb movement (3), reorganize the cortico-reticulo-spinal circuit (4,5), and facilitate locomotor function via modulation of muscle spindle feedback circuits to preserve proprioceptive afferents (6,7). Compared with external assistance from an exoskeleton or physical assistance, EES improves the internal function of an injured spinal cord, thereby partially reestablishing the signal transmission between the brain and the injured spinal cord (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Epidural electrical stimulation (EES) has been reported to restore rhythmic lower‐limb movement (3), reorganize the cortico–reticulo–spinal circuit (4,5), and facilitate locomotor function via modulation of muscle spindle feedback circuits to preserve proprioceptive afferents (6,7). Compared with external assistance from an exoskeleton or physical assistance, EES improves the internal function of an injured spinal cord, thereby partially re‐establishing the signal transmission between the brain and the injured spinal cord (4,5).…”
Section: Introductionmentioning
confidence: 99%